Evidence for the extent and oncological benefit of lymphadenectomy for esophageal cancer - Krauss, Dolores T; Schmidt, Thomas; Bruns, Christiane J; Fuchs, Hans F (Chirurgie (Heidelberg, Germany), 2025)
The prognosis for esophageal cancer is determined in particular by the depth of infiltration (T stage) and lymph node metastasis (N status). In patients with locally advanced tumors, surgical resection is the current standard. The extent of the lymphadenectomy depends on the localization of the tumor, analogous to the choice of surgical technique. For adequate tumor staging and achievement of pN0 status, seven lymph nodes without tumor metastases are necessary by definition but the current guidelines recommend 20 lymph nodes as a benchmark in an expert consensus. Despite the importance of the lymph node status for the prognosis of the patient and the already standardized use of targeted imaging of sentinel lymph nodes in other oncological disciplines, there is neither a validated method nor sufficient evidence for the benefit of lymph node mapping in esophageal cancer. The discussion about the prognostic advantage of lymphadenectomy is particularly interesting in T1 early stage cancer. Due to the technical advances of interventional endoscopy in recent years, organ preservation using endoscopic submucosal dissection (ESD) or endoscopic mucosal resection (EMR) has not only become possible but also safe to carry out and thus established as the standard with better functional results; however, if one or more risk factors are present, endoscopic ablation is no longer defined as curative and should be supplemented by further treatment, usually non-organ-preserving resection. The step from organ-preserving interventional treatment with a low complication rate to a surgical procedure with significant mortality and morbidity as well as functional limitations seems immense and requires optimization, especially in view of the technical developments of surgery in recent years. This can either aim to identify the risk of lymph node metastases more precisely or to minimize the morbidity/mortality and functional limitations of additive treatment procedures. Approaches to this are currently the subject of research and have already been safely applied in individual pilot projects.